The problem of determining the ploughing forces. (12th January 2021) - Popov, Alexey; Krasnikova, Iuliia
Currently, two methods are most often used to determine the ploughing forces: the extrapolation on zero uncut chip thickness and the comparison of total forces at different flank wears. These methods assume that the processes occurring on the front surface of the tool cause no effect on the processes transpiring on the rear surface. This study attempted to prove the connection between these processes, and both methods cannot be used to find the ploughing forces. The results showed that the increase in the uncut chip thickness causes the increase in the ploughing forces. This finding proves the connection between the processes occurring on the front and rear surfaces. To reveal the ploughing forces, we suggest using the third method, the comparison method of the total forces for different contact areas, which is based on the dependence of the processes on the rear surface on the processes on the front surface.